2009
DOI: 10.1016/j.atherosclerosis.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin reduces lipid accumulation in macrophage foam cells

Abstract: Adiponectin is one of several, important metabolically active cytokines secreted from adipocytes. Low circulating levels of this adipokine have been associated epidemiologically with obesity, insulin resistance, type II diabetes, and cardiovascular disease. To determine if adiponectin can modulate lipid metabolism in macrophages, we expressed the adiponectin gene in human THP-1 macrophage foam cells using a lentiviral vector expression system and demonstrated that macrophages transduced with the adiponectin ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 32 publications
(33 reference statements)
6
96
0
5
Order By: Relevance
“…Furthermore, we also found that the reduction of ABCA1 in overweight and obese patients was related to lower circulating level of the antiatherogenic adipokine adiponectin, but not associated with higher levels of the proatherogenic adipokines leptin and resistin. This is in keeping with data from in vitro experiments and animal studies showing that adiponectin can upregulate ABCA1 expression and cholesterol efflux from macrophages, [11][12] and knockout adiponectin can decrease the expression of ABCA1. 12 The activation of peroxisome proliferator-activated receptor g (PPARg) and liver X receptor a (LXRa) is the major mechanism through which macrophage ABCA1 and ABCG1 expression can be upregulated.…”
Section: Abca1 Expression In Obesitysupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we also found that the reduction of ABCA1 in overweight and obese patients was related to lower circulating level of the antiatherogenic adipokine adiponectin, but not associated with higher levels of the proatherogenic adipokines leptin and resistin. This is in keeping with data from in vitro experiments and animal studies showing that adiponectin can upregulate ABCA1 expression and cholesterol efflux from macrophages, [11][12] and knockout adiponectin can decrease the expression of ABCA1. 12 The activation of peroxisome proliferator-activated receptor g (PPARg) and liver X receptor a (LXRa) is the major mechanism through which macrophage ABCA1 and ABCG1 expression can be upregulated.…”
Section: Abca1 Expression In Obesitysupporting
confidence: 88%
“…[9][10] Concerning macrophage RCT, in vitro experiments have shown that adiponectin can upregulate the expression of ABCA1 and cholesterol efflux from human macrophages. [11][12] In adiponectin knockout mice, the expression of ABCA1 and cholesterol efflux from macrophages is decreased compared with wild-type mice. 12 However, whether adiponectin may influence ABCG1 and SR-BI is unclear, and few studies about the effects of adiponectin on cholesterol efflux from macrophages in humans have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, adiponectin strongly induces ABCA1 expression in monocytes, indicating that higher ABCA1 levels are atheroprotective and contribute to enhance cholesterol removal from cells (Tsubakio-Yamamoto et al, 2008). In support of this hypothesis, lentiviral overexpression of adiponectin in macrophages reduces lipid accumulation and enhances cholesterol efflux to apolipoprotein A-I (Tian et al, 2009). In contrast, adiponectin-deficient mice show a significant reduction in ABCA1 and ABCG1 expression which correlates with a decreased cholesterol efflux to apolipoprotein A-I and to a minor extend to HDL, respectively (Tsubakio-Yamamoto et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…Some of its atheroprotective features appear to affect cholesterol homeostasis in peripheral cells, as adiponectin reduces lipid accumulation and, stimulates reverse cholesterol transport in macrophages (Tsubakio-Yamamoto et al, 2008;Tian et al, 2009). Most interestingly, adiponectin strongly induces ABCA1 expression in monocytes, indicating that higher ABCA1 levels are atheroprotective and contribute to enhance cholesterol removal from cells (Tsubakio-Yamamoto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin decreases the ability of LPS or Toll-like receptor activation to elicit TNF and IL-6 production from macrophages [21][22][23][24] and reduces eotaxin expression in bone marrow derived macrophages stimulated with TNF and IL-4 [12]. Adiponectin also inhibits the transformation of macrophages to foam cells [25], which may explain the antiatherosclerotic effects of adiponectin. Cultured alveolar macrophages from adiponectin deficient mice demonstrate increased production of TNF , both innately and upon stimulation with LPS [26].…”
Section: Introductionmentioning
confidence: 99%